What Factors Are Most Closely Associated With Mood Disorders in Adolescents During the COVID-19 Pandemic? A Cross-Sectional Study Based on 1,771 Adolescents in Shandong Province, China - Ren, Ziyuan; Xin, Yaodong; Wang, Zhonglin; Liu, Dexiang; Ho, Roger C. M.; Ho, Cyrus S. H. (Frontiers in Psychiatry, 2021)
Background and Aims: COVID-19 has been proven to harm adolescents’ mental health, and several psychological influence factors have been proposed. However, the importance of these factors in the development of mood disorders in adolescents during the pandemic still eludes researchers, and practical strategies for universal mental health education are limited. Methods: We constructed a sample of 1771 adolescents from six independent middle schools and three independent universities in Shandong province, China. We examined the subjects’ anxiety, depression, psychological resilience, perceived social support, coping strategies, subjective social/school status, screen time, and sleep quality with suitable psychological scales. We chose four widely used classification models—k-nearest neighbors (KNN), logistic regression (LR), gradient-boosted decision tree (GBDT), and a combination of the GBDT and LR (GBDT+LR)—to construct machine learning models, and we utilized the Shapley additive explanations value (SHAP value) to measure how the features affected the dependent variables. The area under the curve (AUC) of the receiver operating characteristic (ROC) curves was used to evaluate the performance of the models. Results: The current rates of occurrence of symptoms of anxiety and depression were 28.3% and 30.8% among the participants. The descriptive and univariate analyses showed that all of the factors included were statistically related to mood disorders. Among the four machine learning algorithms, the GBDT+LR algorithm achieved the best performance for anxiety and depression with average AUC values of 0.819 and 0.857. We found that sleep quality had the closest relation with mood disorders among Chinese adolescents. In addition, according to the feature importance (SHAP value) of the psychological factors, we proposed a five-step universal mental health education strategy to be used during the COVID-19 pandemic (sleep quality—resilience—coping strategy—social support—perceived social status). Conclusion: In this study, we performed a cross-sectional investigation to examine the psychological impact of COVID-19 on adolescents. We applied machine learning algorithms to quantify the importance of each factor. In addition, we proposed a five-step universal mental health education strategy for school psychologists.